Prophylactic plasma transfusion for patients without inherited bleeding disorders or anticoagulant use undergoing non‐cardiac surgery or invasive procedures - Huber, J; Stanworth, SJ; Doree, C; Fortin, PM; Trivella, M; Brunskill, SJ; Hopewell, S; Wilkinson, KL; Estcourt, LJ (Cochrane Collaboration, 2018)
Background: In the absence of bleeding, plasma is commonly transfused to people prophylactically to prevent bleeding. In this context, it is transfused before operative or invasive procedures (such as liver biopsy or chest drainage tube insertion) in those considered at increased risk of bleeding, typically defined by abnormalities of laboratory tests of coagulation. As plasma contains procoagulant factors, plasma transfusion may reduce perioperative bleeding risk. This outcome has clinical importance given that perioperative bleeding and blood transfusion have been associated with increased morbidity and mortality. Plasma is expensive, and some countries have experienced issues with blood product shortages, donor pool reliability, and incomplete screening for transmissible infections. Thus, although the benefit of prophylactic plasma transfusion has not been well established, plasma transfusion does carry potentially life‐threatening risks.